Perturbation Solution to Modified Nonlinear Schrödinger Equation Based on Slowly Varying Envelope Approximation - Ghosh, Arindam; Maitra, Sarit; Chowdhury, Asesh Roy (Journal of Applied Nonlinear Dynamics, 2026)
In this research article a modified nonlinear Schrödinger equation describing the dynamics of slowly varying envelope of electromagnetic waves in plasmas is studied. Applying perturbation technique approximate solutions are obtained and plotted numerically. The effects of the physical parameters on the obtained solutions are also examined.